2013
DOI: 10.5853/jos.2013.15.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Statistics in Korea: Part I. Epidemiology and Risk Factors: A Report from the Korean Stroke Society and Clinical Research Center for Stroke

Abstract: The aim of the Part I of Stroke Statistics in Korea is to summarize nationally representative data of the epidemiology and risk factors of stroke in a single document. Every year, approximately 105,000 people experience a new or recurrent stroke and more than 26,000 die of stroke, which indicates that every 5 minutes stroke attacks someone and every 20 minutes stroke kills someone in Korea. Stroke accounts for roughly 1 of every 10 deaths. The estimated stroke prevalence is about 795,000 in people aged ≥30 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
253
3
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(271 citation statements)
references
References 27 publications
9
253
3
6
Order By: Relevance
“…The occurrence of ischemic stroke in the general population is more frequent in women than in men in the USA, but is less frequent in women than in men in Korea. 32, 33 In addition, Asian AF patients have been shown to have several distinctive features in major randomized controlled trials, including a high risk of bleeding. 17, 18 Second, there may be cultural factors.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of ischemic stroke in the general population is more frequent in women than in men in the USA, but is less frequent in women than in men in Korea. 32, 33 In addition, Asian AF patients have been shown to have several distinctive features in major randomized controlled trials, including a high risk of bleeding. 17, 18 Second, there may be cultural factors.…”
Section: Discussionmentioning
confidence: 99%
“…First, we investigated the stroke age trends between our hospital. So there are some differences in the incidence of HS in our hospital compared with the reports using the national wide data's [11]. Recent reports of national wide data's showed that the mean age of stroke onset has been increased.…”
Section: Discussionmentioning
confidence: 66%
“…In South Korea, the stroke incidence was 216 per 100,000 person-years, and this incidence increased steeply with age; patients of old age comprised the main proportion of strokes. Meanwhile, the relative proportion of HS decreased steadily from 2000 to 2009 (35.3% to 23.9%) [11].…”
Section: Discussionmentioning
confidence: 96%
“…Several studies found that patients who were transported by emergency medical services (EMS) had shorter prehospital delays than did patients who did not use EMS [8][9][10] . In addition, increased IV tPA treatment rate is associated with better prognosis than that achieved by patients not using EMS [3][4][5] . Thus, we speculate that calls to EMS could help solve the problem of prehospital delays, and calls to EMS could be associated with patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent report, each year approximately 105,000 people experience a new or recurrent stroke, and more than 26,000 people die from stroke 2,3) . Patients with stroke must be treated immediately to achieve a good outcome and improve neurological prognosis 4,5) .…”
Section: Introductionmentioning
confidence: 99%